Organizational gift: gift at distance and circuits of commerce - Steiner, Philippe (Tempo Social, 2017)
This article examines the characteristics of the organizational gift: a specific form of gift in which an organization or a series of organizations steps in between the donor and the donee. After a comparison with the Maussian gift, this article examines three key characteristics of the organizational gift: the role played by the organization which prevents direct contact but connects people at distance; the circuits of commerce thank to which resource move from the donator to the donee and, finally, the issue raised by the difficulty to give back in the absence of a direct link between the donator and the donee. The conclusive part stresses the role played by organizational gifts in producing a solidarity at distance between human beings.